Metallurgical Analysis of Steel Plate for Deep Drawing Application - Victor Yuardi Risonarta; Huffal Azhar Fadly; Hafidh Frian Perdana (Institute of Research and Community Outreach - Petra Christian University, 2017)
Deep drawing is one of metal forming manufacturing processes which can be used to produce many products, e.g. kitchen ware, automotive parts, etc. Although this particular manufacturing company has applied the Japanese standard JIS G 3141 as guidance to select a steel plate for deep drawing application, the deep drawing process at this company is still failed. Therefore, this manuscript discusses more deeply the metallurgical analysis of selected steel plates to produce a deep-drawn product with 0.5 thickness. Analysis presented in this manuscript comprises the influence of chemical composition of a steel plate on its mechanical property, i.e., tensile strength, elongation, and hardness. As a result, a correlation between chemical composition and expected mechanical property to manufacture a drink cup is outlined. Moreover, recommended chemical composition of a steel plate is also presented.